Design and Implementation of a Final Project Plagiarism Detection System Using Cosine Similarity Method - Rival Fauzi; Muhammad Iqbal; Tita Haryanti (IJAIT (International Journal of Applied Information Technology), 2021)
Plagiarism is an act of taking ideas, taking research results, acquiring research results, and summarizing writing without mentioning the source, either intentionally or unintentionally. The cosine similarity method can be used to calculate the score of similarities between documents by comparing existing documents on the database with uploaded ones to gain a similarity percentage. External plagiarism detection (EPD) is used to compare the contents of articles. The design and implementation of the system will be carried out in several stages in the hope that the system can work optimally and detect text similarities accurately. This research objective is to check the plagiarism rate of the document using the cosine similarity method as a method of calculating word equations called Kipcheck. The purpose of checking the level of plagiarism is to ensure that the documents created have a minimum level of fraud to avoid academic sanctions. Kipcheck uses three application system tests; maximum word calculation that can be processed; comparing application and manual calculation; and testing the consistency of application calculation results based on two different schemes.